2012
DOI: 10.1186/1471-2229-12-145
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetyltransferases in rice (Oryza sativaL.): phylogenetic analysis, subcellular localization and expression

Abstract: BackgroundHistone acetyltransferases (HATs) play an important role in eukaryotic transcription. Eight HATs identified in rice (OsHATs) can be organized into four families, namely the CBP (OsHAC701, OsHAC703, and OsHAC704), TAFII250 (OsHAF701), GNAT (OsHAG702, OsHAG703, and OsHAG704), and MYST (OsHAM701) families. The biological functions of HATs in rice remain unknown, so a comprehensive protein sequence analysis of the HAT families was conducted to investigate their potential functions. In addition, the subce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
97
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 81 publications
9
97
0
Order By: Relevance
“…Histone acetylation has been demonstrated to function in different plant hormones (23,(26)(27)(28)(29), and several histone deacetylases are known to be involved in the regulation of gene expression (30)(31)(32)(33)(34)(35)(36)(37). The data presented here showed that the C-terminal domain of EIN2 (EIN2-C) is the key factor that drives alterations in histone acetylation during the ethylene response.…”
Section: Discussionmentioning
confidence: 65%
“…Histone acetylation has been demonstrated to function in different plant hormones (23,(26)(27)(28)(29), and several histone deacetylases are known to be involved in the regulation of gene expression (30)(31)(32)(33)(34)(35)(36)(37). The data presented here showed that the C-terminal domain of EIN2 (EIN2-C) is the key factor that drives alterations in histone acetylation during the ethylene response.…”
Section: Discussionmentioning
confidence: 65%
“…This decondensed pattern is related to high transcriptional activity at this developmental stage . Histone acetylation is normally correlated with an increased gene activity [Liu X et al, 2012]. DNA methylation and H4 deacetylation act simultaneously and coordinately, restructuring the chromatin and regulating the gene expression during floral differentiation [Meijón et al, 2009].…”
Section: H3ac and H4ac Change During Microspore Embryogenesis In Relamentioning
confidence: 99%
“…Acetylation of lysines in histones has been recognized as a characteristic of actively transcribed genes by altering histone-DNA interactions and making the DNA more accessible to the transcription machinery [Xu et al, 2005;Earley et al, 2007]. N-terminal lysine residues of histones H3 and H4 are found to be acetylation targets for different histone acetyltransferases (HATs), enzymes which contribute to many plant development and adaptation processes in combined action with histone deacetylases [Pandey et al, 2002;Xu et al, 2005, Liu X et al, 2012. Changes in chromatin condensation-decondensation states have been reported at different developmental stages during microspore embryogenesis in relation to changes in chromatin function and cell activity [Testillano et al, 2000.…”
mentioning
confidence: 99%
“…By contrast, deacetylation induces a more compact chromatin structure that is associated with transcriptional repression. Histone acetylation mediates the effects of various plant hormones (Pandey et al, 2002;Liu et al, 2012;Yamamuro et al, 2016), and several histone deacetylases are known to be involved in the regulation of gene expression in plants (Zhou et al, 2005;Zhu et al, 2011;Perrella et al, 2013;Wang et al, 2013). Little is known about histone acetyltransferases or HDACs in ethylene signaling, however.…”
Section: Discussionmentioning
confidence: 99%